Ion Pairing and Outer Sphere Effect - Viktor Gutmann (CHIMIA)
Ion-ion and ion-solvent interactions are presented from the point of view of the donor-acceptor concept. The solvent donor properties are characterised by the donor number and the solvent acceptor properties by the acceptor number. Formation of ions is considered as a substitution reaction. It is suggested to apply the terms “ion-pair” and “ion-association” only as long as the ions retain essentially their structural identies. Various processes hitherto referred to ion pairing or ion association are re-interpreted in terms of “outer-sphere’’-complexation. The outersphere effects are formulated for the changes in inner-sphere bond distances. They are applied to various ion-ion interactions, such as [Fe(CN)6]3-∙[Bu4N]+. The inconsistencies of the “contact ion pair”-concept are demonstrated including its application to phenomena involving hydrogen bonding. A simplified reaction scheme based on the donor-acceptor concept is presented for ion-ion as well as for ion-solvent interactions.